2018
DOI: 10.1016/j.biopsycho.2018.05.016
|View full text |Cite
|
Sign up to set email alerts
|

Cortical hypoactivation during resting EEG suggests central nervous system pathology in patients with chronic fatigue syndrome

Abstract: We investigated central fatigue in 50 patients with chronic fatigue syndrome (CFS) and 50 matched healthy controls (HC). Resting state EEG was collected from 19 scalp locations during a 3 min, eyes-closed condition. Current densities were localized using exact low-resolution electromagnetic tomography (eLORETA). The Multidimensional Fatigue Inventory (MFI-20) and the Fatigue Severity Scale (FSS) were administered to all participants. Independent t-tests and linear regression analyses were used to evaluate grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 127 publications
(159 reference statements)
0
29
0
1
Order By: Relevance
“…Females made up the largest proportion of participants. There were only 10 studies which reported race, where majority of the participants were Caucasian [12,19,21,26,27,37,41,47,48,52]. Mean age across all studies was 40.9 years for ME/CFS patients and 39.07 years for HCs.…”
Section: Participant and Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Females made up the largest proportion of participants. There were only 10 studies which reported race, where majority of the participants were Caucasian [12,19,21,26,27,37,41,47,48,52]. Mean age across all studies was 40.9 years for ME/CFS patients and 39.07 years for HCs.…”
Section: Participant and Study Characteristicsmentioning
confidence: 99%
“…In all twin studies, levels of zygosity were assessed and ascertained at 99.9% [12,21,27]. 47 of the 55 identified papers included participants that fulfilled the requirements of being diagnosed with the Fukuda criteria [12,14,[16][17][18][19][21][22][23][24][25][26][27][28]30,31,[34][35][36][37][38][39][40][41][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61]. Three of the papers used the more stringent CCC criteria to classify ME/CFS patients [15,29,42].…”
Section: Participant and Study Characteristicsmentioning
confidence: 99%
“…1 There was plenty of literature available, especially more recently, which added growing support for a neuro-inflammatory concept to explain ME/CFS. 5,6 Most of the evidence involved either brain scanning techniques [7][8][9][10][11] or cerebrospinal fluid studies of ME/CFS patients, [12][13][14][15] but it was evident that the brain scanning technology being used was simply not sophisticated enough to detect chronic and fluctuating inflammation in the brains of ME/CFS patients that mirrored the chronic and fluctuating symptoms described above.…”
Section: Making Sense Of My Conditionmentioning
confidence: 99%
“…Причина может заключаться в нарушении работы центральной нервной системы. Так, при электроэнцефалографии в группе пациентов с СХУ выявлена умеренная гипоактивация коры по сравнению с данными здоровых людей [7]. Возможно и некоторое снижение индивидуальной эмоциональной устойчивости, так как у многих пациентов появление симптомов совпадает со стрессорным фактором (травма, семейные сложности и др.)…”
Section: Introductionunclassified